2021
DOI: 10.3390/su13158365
|View full text |Cite
|
Sign up to set email alerts
|

Determining Factors Affecting Acceptance of E-Learning Platforms during the COVID-19 Pandemic: Integrating Extended Technology Acceptance Model and DeLone & McLean IS Success Model

Abstract: Online meeting platforms have been widely utilized during the COVID-19 pandemic due to the current shift from traditional learning. However, the acceptance of the different online meeting platforms for e-learning has been underexplored. The purpose of this study was to determine the factors for acceptance of an online learning platform among students during the COVID-19 pandemic. A total of 500 senior high school students voluntarily participated to answer constructs under the Extended Technology Acceptance Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 49 publications
2
75
5
2
Order By: Relevance
“…The application is clear, understandable, easy to use, and accurate information is received upon using the application. Both PU and PEU have been investigated to have synergistic effects that lead to AU with the TAM [ 50 ]. Similarly, Camacho-Rivera et al [ 30 ] found that 21.8% of US citizens use COVID-19 trackers due to usefulness and PEU.…”
Section: Discussionmentioning
confidence: 99%
“…The application is clear, understandable, easy to use, and accurate information is received upon using the application. Both PU and PEU have been investigated to have synergistic effects that lead to AU with the TAM [ 50 ]. Similarly, Camacho-Rivera et al [ 30 ] found that 21.8% of US citizens use COVID-19 trackers due to usefulness and PEU.…”
Section: Discussionmentioning
confidence: 99%
“… Innovation Diffusion Theory (IDT) proposed by Rogers ( 1962 , 1995 ) as the most popular model in investigating innovation acceptance and adoption (N=2), specifically (Lee et al, 2011 ; Al-Rahmi, Yahaya, Aldraiweesh, Alamri, Aljarboa, Alturki & Aljeraiwi, 2019), Information Systems Success Model (ISSM) introduced by DeLone and McLean ( 1992 ) as a robust theoretical basis for the study of technology post-adoption (N=2), specifically (Prasetyo et al, 2021 ; Al-Rahmi et al, 2021 ), combination of ISSM and Expectation-Confirmation Theory (ECT), a post-adoption theory offered by Oliver ( 1980 ), in work conducted by Roca, Chiu, and Martinez ( 2006 ). …”
Section: Resultsmentioning
confidence: 99%
“…Information Systems Success Model (ISSM) introduced by DeLone and McLean ( 1992 ) as a robust theoretical basis for the study of technology post-adoption (N=2), specifically (Prasetyo et al, 2021 ; Al-Rahmi et al, 2021 ),…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of information available on platforms impacts user satisfaction and related decision making considerably [8,9]. Therefore, the present study will guide users to share and choose high-quality travel answer content and help platforms to screen for highquality answers according to the travel information required.…”
Section: Introductionmentioning
confidence: 99%